2009
DOI: 10.1086/605056
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Prospective Study on the Burden of Rotavirus Gastroenteritis in Turkey, 2005–2006: A Hospital‐Based Study

Abstract: Rotavirus is the main cause of gastroenteritis and dehydration requiring hospitalization among infants and children. Despite the high diarrhea-related mortality rate, there are limited studies describing the prevalence of rotavirus in Turkey. The disease burden of rotavirus gastroenteritis in Turkey was assessed by active, prospective surveillance conducted in accordance with a modified World Health Organization generic protocol from 1 June 2005 through 1 June 2006. A total of 411 children aged <5 years who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 16 publications
8
49
0
9
Order By: Relevance
“…In studies done by other groups, they found high incidence of rotavirus gastroenteritis between December to April. 19 Confirming our result, we found that peak incidence was in January and February (38.6%) followed by March and April (36.4%), and significantly lower incidence of infection was detected in May and June (13%) (p<0.05). Peak incidence during winter and spring seasons is possibly due to the moist and relatively cold period which might support viral stability in such climate.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In studies done by other groups, they found high incidence of rotavirus gastroenteritis between December to April. 19 Confirming our result, we found that peak incidence was in January and February (38.6%) followed by March and April (36.4%), and significantly lower incidence of infection was detected in May and June (13%) (p<0.05). Peak incidence during winter and spring seasons is possibly due to the moist and relatively cold period which might support viral stability in such climate.…”
Section: Discussionsupporting
confidence: 89%
“…17 On national level, our data (32%) were close to it, as well as to that obtained and recorded in Thi-Qar (39%), 21 but surprisingly they were much lower than that recorded in Najaf (66.7%). 22 Comparably, the results were also close to that reported in Jordan (33%) 23 and Turkey (32.4%), 19 the neighboring countries. The results also revealed that the incidence of rotavirus infection was significantly higher in urban (33.6%) areas compared to that observed among children from rural (24.7%) areas.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Bizim çalışmamızda elde edilen toplam pozitiflik oranı (%38.7), bu araştırıcıların 9 sonucuna (%42.9) yakın olmasına karşın, viral etkenlerin sıklık derecelerinde farklılık gözlenmiş ve ilk sırayı noroviruslar (6 GII+2 GI; 8/31, %25.8) alırken onu rotavirus grup A (2/31, %6.5) izlemiştir. Ülkemizde son yıllarda yapılan çalışmalar değerlendirildiğinde ise, gastroenteritli çocuklarda rotavirus pozitiflik oranlarının (çoğu antijen testleri ile alınan sonuçlar olmak üzere) %18-53 arasında olduğu görülmektedir [21][22][23][24][25][26][27][28] . Bizim çalış-mamızda rotavirus saptanma oranının (%6.5) bu çalışmalardan daha düşük bulunması, kullanılan yöntemlerin farklılığından ve bölgesel farklılıklardan kaynaklanmış olabilir.…”
Section: Tanımlanan Virusların Toplam öRnek Sayısına Oranı* (N= 50)unclassified